2017
DOI: 10.7575/aiac.alls.v.8n.2p.170
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship between the IELTS Listening and Listening in Academic English Programs

Abstract: The challenge for many teachers teaching in academic English programs is, on the one hand, to actualize the objectives of their course and on the other hand, prepare their students for the important international tests such as IELTS and TOEFLE. The current study seeks to reconcile this challenge by drawing on the relationship between the IELTS listening and listening in academic English programs. The requirements of the two domains were compared through a semi – structured interview with five participating aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Most of them have examined the relevance of a specific IELTS sub-skill to academic study at university. With respect to listening, Sabet and Babaei (2017) found that academic listening and IELTS listening tasks were different in terms of pragmatic understanding, the integration of skills, multiplicity of texts for listening, information literacy, and the concept of construct irrelevant variance. In terms of reading, Kovalenko (2018) reported that although preparing for the IELTS reading test could help to improve students’ concentration, anxiety control, and decision-making speed when reading academic texts, it did not significantly contribute to success in academic reading tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them have examined the relevance of a specific IELTS sub-skill to academic study at university. With respect to listening, Sabet and Babaei (2017) found that academic listening and IELTS listening tasks were different in terms of pragmatic understanding, the integration of skills, multiplicity of texts for listening, information literacy, and the concept of construct irrelevant variance. In terms of reading, Kovalenko (2018) reported that although preparing for the IELTS reading test could help to improve students’ concentration, anxiety control, and decision-making speed when reading academic texts, it did not significantly contribute to success in academic reading tasks.…”
Section: Introductionmentioning
confidence: 99%